2017
DOI: 10.1371/journal.pone.0177893
|View full text |Cite
|
Sign up to set email alerts
|

Familial breast cancer: Genetic counseling over time, including patients´ expectations and initiators considering the Angelina Jolie effect

Abstract: PurposeThe German Consortium for hereditary breast/ovarian cancer (GC-HBOC) aims for nationwide access to professional, individualized yet structured care for families at high risk. The identification of such families remains key for optimal care. Our study evaluates counselees’ characteristics, referral practices, expectations and motivations in respect to their first genetic consultation. The impact of the Angelina Jolie Effect (AJE) was prospectively assessed.MethodsAll counselees could participate through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In the majority of cases (78.7% (942/1197)), the reason for referral was a personal or family history of Breast and/or Ovarian cancer and affected individuals were tested within 1 year of diagnosis. This is indicative of a bigger awareness in terms of preventive diagnosis for this tumor type, especially following the publicity received by the BRCA1 and BRCA2 genes due to the “Jolie effect” [42, 43]. Variant analysis revealed the presence of at least one clinically significant variant in 22.1% of the individuals analyzed, while a VUS was identified in 34.8% (417/1197) of the cases.…”
Section: Discussionmentioning
confidence: 98%
“…In the majority of cases (78.7% (942/1197)), the reason for referral was a personal or family history of Breast and/or Ovarian cancer and affected individuals were tested within 1 year of diagnosis. This is indicative of a bigger awareness in terms of preventive diagnosis for this tumor type, especially following the publicity received by the BRCA1 and BRCA2 genes due to the “Jolie effect” [42, 43]. Variant analysis revealed the presence of at least one clinically significant variant in 22.1% of the individuals analyzed, while a VUS was identified in 34.8% (417/1197) of the cases.…”
Section: Discussionmentioning
confidence: 98%
“…The demand for clinical cancer genetics services has grown rapidly in recent years, mainly as a result of raised awareness both within the medical community and among the general population (Evers et al 2017;Juthe et al 2015). Furthermore, the influence of germline genetic testing on treatment-based decisions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies have reported an increase in referrals due to the so-called Angelina Jolie effect [18, 19]. The BC patients in our study were diagnosed between 2000 and 2013.…”
Section: Discussionmentioning
confidence: 60%